2018
DOI: 10.1590/1983-40632018v4853165
|View full text |Cite
|
Sign up to set email alerts
|

Idioblasts formation and essential oil production in irrigated Piper aduncum

Abstract: The growing of Piper aduncum for essential oil extraction has increased, but there is a lack of basic information about its management and cultivation, which allows the productivity and quality of the oil, in order to attend the market demands. This study aimed to evaluate the relation between the production of essential oils from P. aduncum and soil water pressure heads (20 kPa, 40 kPa, 60 kPa, 100 kPa and non-irrigated). The assessment comprised the quantification of idioblasts and the production of essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Several research groups have identified several important properties in the control of agricultural pests in the essential oil of this species, such as the insecticide (Krinski et al 2018) and fungicide properties (Valadares et al 2018). Despite the relevance of P. aduncum, its commercial exploration is still limited to experimental plantations and management of native populations (Jacinto et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups have identified several important properties in the control of agricultural pests in the essential oil of this species, such as the insecticide (Krinski et al 2018) and fungicide properties (Valadares et al 2018). Despite the relevance of P. aduncum, its commercial exploration is still limited to experimental plantations and management of native populations (Jacinto et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Plants of P. aduncum grown in pots and subjected to moderate water suppression for eight days had an increase in the contents of photosynthetic pigments and essential oils but did not change the production of dry mass (Pacheco et al 2022). Under field conditions, the cultivation of P. aduncum in rainfed conditions provided a 62% reduction in essential oil contents compared to irrigated environments, however, excess water was also harmful (Jacinto et al 2018). In a degraded area subjected to water deficit, P. aduncum was considered one of the most sensitive to transplantation due to lower survival and seedling height after 12 months (Oliveira et al 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…In the essay by Pacheco et al (2022), only a punctual moderate drought event was considered, a factor that may have contributed to the lack of visualization of the effect on dry mass accumulation. On the other hand, in the studies by Jacinto et al (2018) and Oliveira et al (2021b), the tests were carried out in the field, and environments were subject to periods of recurrent drought and rehydration, providing indications that recurrent drought can harm plant development.…”
Section: Introductionmentioning
confidence: 99%